Accuracy in estimating project cost construction contingency - a statistical analysis - Baccarini, David (2004)
The cost performance of building construction projects is a key success criterion for project sponsors. Project cost performance is typically measured by comparing final cost against budget. A key component of the project budget for the construction contract is construction contingency, which caters for contract variations that arise during the implementation phase of projects. It is important for project sponsors to know the level of accuracy being achieved in estimating construction contingency. Statistical analysis of past projects provides a means for measuring the accuracy of construction contingency. The cost data for 48 road construction projects completed by an Australian government organisation were statistically analysed to investigate the accuracy of contingency. It was found that the average construction contingency was 5.24% of the Award Contract Value but the average value of contract variations was 9.92%. The organisation used a traditional percentage approach for estimating construction contingency. This suggests that the organisation has room to improve the accuracy of its construction contingency estimates by seeking alternative estimating methods. An investigation of an alternate estimating approach derived from the analysis of the data found that there were no significant correlations between project variables and construction contingency that might be used to create a prediction model for construction contingency.